Toxicology studies of aqueous-alcohol extracts of Harpagophytum procumbens subsp. procumbens (Burch.) DC.Ex Meisn. (Pedaliaceae) in female and male rats - Kirtan Joshi; Alan Parrish; Elizabeth A. Grunz-Borgmann; Mary Gerkovich; William R. Folk (BMC, 2020)
Abstract Background A variety of medicinal products prepared from secondary tubers of Harpagophytum procumbens subsp. procumbens (Burch.) DC.ex Meisn. (Devil's Claw) and H. zeyheri are marketed in Africa, Europe, the United States, South America and elsewhere, where they are used for inflammatory and musculoskeletal conditions such as arthritis, lower back pain, rheumatism and neuralgia, etc. While clinical studies conducted over the last twenty years support the general safety of such products, infrequent gastrointestinal disturbances (diarrhea, nausea, vomiting, abdominal pain), headache, vertigo and hypersensitivity (allergic) reactions (rash, hives and face swelling) have been documented. Sex-related differences occur in the health conditions for which Devil's Claw products are used, so it is likely that usage is similarly sex-related and so might be side effects and potential toxicities. However toxicologic studies of Devil's Claw products have been conducted primarily with male animals. To address this deficit, we report toxicological studies in female and male rats of several H. procumbens (HP) aqueous-alcohol extracts chemically analyzed by UPLC-MS. Methods Female and male Sprague Dawley rats were studied for one and three months in groups differing by consumption of diets without and with HP extracts at a 7-10-fold human equivalent dose (HED). Sera were analyzed for blood chemistry, and heart, liver, lung, kidney, stomach, and small and large intestine tissues were examined for histopathology. Treatment group differences for blood chemistry were analyzed by ANOVA with Dunnett's test and significant group differences for endpoints with marginal distributional properties were verified using the Kruskal-Wallis test. Group differences for histopathology were tested using Chi Square analysis. Results Significant group by sex-related differences in blood chemistry were detected in both studies. Additionally, several sex-related differences occurred between the studies. However, significant histopathology effects associated with the consumption of the extracts were not detected. Conclusion Toxicologic analysis of Devil's Claw extracts cause significant sex-related effects in blood chemistry. However, in our judgement, none of the observed effects suggest serious toxicity at these doses and durations. Subsequent toxicologic and clinical studies of H. procumbens and other medicines with similar properties should explore in greater detail the basis and consequences of potential sex-related effects.